SIMULATION OF OCEANIC BOTTOM PRESSURE FOR GRAVITY SPACE MISSIONS - Wunsch J.; Thomas M.; Gruber Th. (My University, 2001)
Oceanic bottom pressure is affected by mass redistribution in the ocean and atmosphere, and it influences gravity field determinations by the new satellite missions CHAMP, GRACE and GOCE from seasonal up to short-period timescales. Thus, mass redistribution in the ocean needs to be accounted for to obtain the mean gravity field. With the Hamburg ocean model for circulation and tides (OMCT), time-dependent oceanic bottom pressure fields are calculated using atmospheric fluxes of momentum, heat and freshwater from ECHAM3 real-time simulations. The resulting bottom pressure fields are expanded in gravity field spherical harmonic coefficients as a function of time. The temporal resolution is 5 days for extracting annual and semi-annual amplitudes and 6 hr for studying high-frequency variations. In order to estimate the influence of oceanic mass variations on gravity field determination, degree variance spectra of simulated bottom pressure are calculated and compared with the expected error spectra of space missions. Furthermore, variations in geoid height ΔN from the modelled Stokes coefficients are illustrated. The numerical results suggest that ocean-induced long-wavelength gravity variations become detectable with the CHAMP and GRACE gravity missions.
Keywords: OCEAN CIRCULATION; STOKES COEFFICIENTS; TIME-VARIABLE GRAVITY FIELD